The Influence of Leadership and Workload on Nutritionist Performance with Motivation as an Intervening Variable - Angrenggani, Dhenok Widari; Lestari, Sri; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (INNOVATION RESEARCH JOURNAL, 2025)
his study to analyze the influence of leadership, workload on nutritionists performance at PuskesmasSurabaya with motivation as an intervening variable. Type of research is quantitative research with apopulation of all nutritionists at Puskesmas Surabaya totaling 63 people. Analysis used is descriptivestatistical analysis, outer model analysis and structural inner model using SmartPLS 4.0 software.Research data was obtained by distributing questionnaires, after data collection was completed, dataprocessing was carried out to determine whether there was an influence on the variables studied withemployee performance. The results of this study indicate that 1.the leadership variable has a negative andinsignificant influence on employee performance, 2.the workload variable has a positive and insignificantinfluence on employee performance, 3.the leadership variable has a positive and insignificant influence onperformance, 4.the workload variable has a positive and significant influence on performance, 5.themotivation variable has a positive and significant influence on performance, 6.motivation is not able tomediate the relationship between leadership and nutritionist performance, 7.motivation is able to mediatethe relationship between workload and nutritionist performance